Native turncoats and indirect facilitation of species invasions. Issue 1871 (24th January 2018) - Northfield, Tobin D.; Laurance, Susan G. W.; Mayfield, Margaret M.; Paini, Dean R.; Snyder, William E.; Stouffer, Daniel B.; Wright, Jeffrey T.; Lach, Lori
Abstract : At local scales, native species can resist invasion by feeding on and competing with would-be invasive species. However, this relationship tends to break down or reverse at larger scales. Here, we consider the role of native species as indirect facilitators of invasion and their potential role in this diversity-driven 'invasion paradox'. We coin the term 'native turncoats' to describe native facilitators of non-native species and identify eight ways they may indirectly facilitate species invasion. Some are commonly documented, while others, such as indirect interactions within competitive communities, are largely undocumented in an invasion context. Therefore, we use models to evaluate the likelihood that these competitive interactions influence invasions. We find that native turncoat effects increase with the number of resources and native species. Furthermore, our findings suggest the existence, abundance and effectiveness of native turncoats in a community could greatly influence invasion success at large scales.